The adult stages of Nanomis and Spiritiops (Ephemeroptera: Baetidae) - Salles, Frederico Falcão (2008)
The adult stages of Nanomis Lugo-Ortiz & McCafferty and Spiritiops Lugo-Ortiz & McCafferty are described for the first time based on reared material from Argentina and Brazil, respectively. They can be differentiated from the other adults of Baetidae by the following characters: Nanomis, hind wings with three longitudinal veins, second vein bifurcate; costal projection of the hind wings pointed, placed in the basal third of anterior margin; and forceps three-segmented, third segment rounded. Spiritiops, fore wings with paired and long marginal intercalary veins; hind wings with three complete longitudinal veins, and an incomplete small longitudinal vein; costal projection of hind wings pointed, broad at base and placed in the basal third of anterior margin; forceps three-segmented, second segment constricted and third segment elongate and narrowed.